Endoplasmic Reticulum Stress Affects Cholesterol Homeostasis by Inhibiting LXRα Expression in Hepatocytes and Macrophages - Wang, Tian (Nutrients, 2020)
Atherosclerosis (AS) is the most common cardiovascular disease, and reverse cholesterol transport (RCT) plays an important role in maintaining cholesterol homeostasis. Both endoplasmic reticulum (ER) stress and LXRα can affect the metabolism of cholesterol. However, whether ER stress can modulate cholesterol metabolism by LXRα in hepatocytes and macrophages remains unclear. Therefore, in this study, we aimed to explore the relationship between ER stress induced by tunicamycin and LXRα in hepatocytes and macrophages and clarify their possible mechanisms and roles in AS. C57BL/6 mice and Huh-7 and THP-1 cells were treated with tunicamycin and LXR-623 (an agonist of LXRα) alone or in combination. Tunicamycin-induced ER stress caused liver injury; promoted the accumulation of cholesterol and triglycerides; inhibited the expression of LXRα, ABCA1 and ABCG1 in the livers of mice, thus reducing serum high-density lipoprotein (HDL)-C, low-density lipoprotein (LDL)-C, total cholesterol and triglyceride levels; however, LXR-623 could attenuate ER stress and reverse these changes. We also obtained the same results in Huh-7 and THP-1 cells. ER stress induced by tunicamycin could clearly be reversed by activating LXRα because it promoted cholesterol efflux by enhancing the expression of ABCA1 and ABCG1 in hepatocytes and macrophages, contributing to attenuation of the development of AS.